BIS-Guided Total Intravenous Anesthesia for Orchiopexy and Circumcision in a Child with Severe Autism: A Case Report. (21st November 2012) - Okur, Selçuk; Arıkan, Müge; Temel, Gülşen; Temel, Volkan
Abstract : Autistic children are very difficult to manage in the hospital setting because they react badly to any change in routine. We describe a case of 10-year-old male patient with severe autism undergoing orchidopexy and circumcision. Following premedication, anesthesia was induced with remifentanil, propofol, atracurium, and maintained with total intravenous anesthesia (propofol and remifentanil). The Bispectral Index System was monitored for determination of the depth of anesthesia. After surgery, all infusions were discontinued. The patient was then transferred to the postanesthetic care unit. There were no adverse events observed during the anesthetic management. The patient was discharged from the hospital on the second postoperative day. Bispectral Index System-guided Total Intravenous Anesthesia can provide some advantages for patient with autism, such as hemodynamic stability, early and easy recovery, to facilitate faster discharge, to optimize the delivery of anesthetic agents, to minimize its adverse effects, and to maximize its safety.